Explosive range expansion of Eulophia graminea (Orchidaceae) in Puerto Ricio and the West Indies - Ackerman, James D.; González-Orellana, Normandie (Lankesteriana: International Journal on Orchidology, 2021)
Eulophia graminea Lindley (Orchidaceae), a native orchid of tropical and subtropical Asia, was first reported in the Western Hemisphere from populations in Miami, Florida, U.S.A. where it spread rapidly through the southern part of the state. Here we report the first record of this species for Puerto Rico and sightings in the Bahamas and Cuba, reflecting the rapid spread seen in southern Florida (U.S.A).